Determination of Oil Quality and Antifungal Effect of Selected Citronella Accessions (Cymbopogon nardus, Cymbopogon winterianus) to Formulate an Anti-Dandruff Shampoo - Wijerathna, Rathnayaka Mudiyanselage Nipuni; Wijeweera, Achini Anuradha; Wijethunga, Anushi Madushani; Mapa, Mapa Mudiyanselage Sumudu Tharangani (Biology, Medicine, & Natural Product Chemistry, 2023)
Citronella is an aromatic grass of the family Poaceae which can be classified into two categories Ceylon Citronella (Cymbopogon nardus) and Java Citronella (Cymbopogon winterianus).  The Citronella oil was extracted from five selected Ceylon Citronella (HP T1, HP T2 and HP T3) and Java Citronella (MP T1 and MP T2) accessions using steam distillation and hydrodistillation methods. Citronella oil quantity extracted by hydrodistillation with Xylene from Ceylon Citronella was higher (2.45-2.67 mL/100 g) than the Java Citronella (1.57-1.64 mL/100 g). The oil quantity of Ceylon Citronella (HP T1-5.52 %, HP T2- 1.40 %, HP T3- 1.05 %) and the quantity of Java Citronella (MP T1- 1.25%, MP T2- 1.79%) extracted by hydrodistillation showed a significant difference (P<0.0001) and there was no significant difference (P=0.7055) between the oil quantity of Ceylon (HP T1- 1.07%, HP T2- 1.18 %, HP T3- 1.19%) and Java (MP T1- 1.16%, MP T2- 1.23%) oils extracted by the steam distillation. Both Java and Ceylon Citronella oils showed organoleptic properties with pale yellow to pale brownish yellow colour and a strong citrusy aroma which meets the ISO 3848 and ISO 3849 standards. The oil of Ceylon Citronella accessions showed refractive index (1.465-1.487), relative density (0.893-0.910), and ethanol solubility (1:2 mL) within the ranges specified in SLS 170 standards. Java Citronella oil exhibited the refractive index (1.4660-1.4730), relative density (0.880-0.892), ethanol solubility (1:2 mL), and optical rotation (-5? to 0?) which meets the specifications of ISO 3848 standards. Geraniol, Citronellol, and Citronellal were identified as the major constituents using the gas chromatography-mass spectrometry (GC-MS) where Java Citronella oil showed high Geraniol content (48.60-49.17%) than Ceylon Citronella oil (16.93-26.49%). All types of tested Citronella oil showed inhibition against Candida albicans where HP T3 (1.9 cm) and MP T1(2.0 cm) oils showed the highest promising antifungal activity among Ceylon oils and Java oils respectively. Therefore, these two oils were selected for the antidandruff shampoo formulation. The two antidandruff shampoo samples were formulated with 2% v/v concentrations of HP T3 and MP T1 Citronella oil which were determined as MIC for the inhibition of C. albicans. Antidandruff shampoo tested against C. albicans showed greater antifungal activity (HP T3 - 2.5±0.05 cm; MP T1 - 2.5±0.05 cm) than the crude Citronella oil (HP T3- 1.9±0.11 cm; MP T1-2.0±0.1 cm), also attained the organoleptic and physical properties such as pH (4.0-8.0), foam height (>100 mL), dirt dispersion (no ink in foam), viscosity, low wetting time and solid content (HP T3-14.75±0.12%; MP T2-12.33±0.19%) in acceptable specification range. This study exhibits that Ceylon Citronella oil HP T1 has the highest oil quantity from all selected accessions.  Hydrodistillation can be used to extract high oil quantity than the steam distillation method from both Java and Ceylon Citronella types. Compared to Ceylon Citronella oil, Java oil has significant potential industrial applications with high Geraniol content and with the highest antifungal activity against C. albicans. Also, the tested Citronella oil of all selected accessions of both Java and Ceylon types meet the organoleptic and physiochemical requirements specified by the ISO and SLS quality standards with excellent antifungal activity against C. albicans, which provides prospective to use Citronella oil as a natural, safe, and eco-friendly fungicide in future product formulations.